Review on Economy and Social System in Central in the Kushan Period: A Comprehensive Analysis of the Economy and Social System during the Kushan Period in Northern India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present work makes an attempt to undertake a micro study of the economic life in northern India during the rule of the Kusanas in India. To make the work comprehensive in nature we have studied all the works on the subject by modern scholars carefully noting their observations and findings. Thereafter we surveyed many of the original texts (with their translations) which are relevant for our study in order to have a peep into the injunctions laid down by them. We have surveyed and analysed various inscriptions of the Kusanas and their contemporaries. Coins of the Kusanas recovered from different parts of India are also adequately utilised. The focus of this work is to analyse different aspects of the economic life of northern India during the rule of the Kusanas which include the currency system of the Kusanas, agrarian system during the Kusana period and the assessment of the land revenue, various industries producing during the early centuries of the Common Era, various internal and external trade routes active during the Kusana period, various commodities in which the trade was carried on, guilds and their 1 activities, various towns and cities in northern India and the impact of the Kusana economy on the living standard of the people etc.